Demography of the bottlenose dolphin Tursiops truncatus (Mammalia: Delphinidae) in the Eastern Ligurian Sea (NW Mediterranean): quantification of female reproductive parameters. Issue 1 (1st January 2017) - Rossi, A.; Scordamaglia, E.; Bellingeri, M.; Gnone, G.; Nuti, S.; Salvioli, F.; Manfredi, P.; Santangelo, G.
Abstract: The reproductive histories of 41 adult bottlenose dolphin females were analysed using photo-identification data collected between 2006 and 2014 in four sub-areas of the eastern Ligurian Sea (northwest Mediterranean). The Rapallo sub-area revealed the highest (highly significant) frequency of encounters (per unit effort) of reproductive females in association with young individuals, therefore emerging as a candidate nursery area in the region. The estimated fertility rate of adult females ranged between 290 and 407 births per 1000 individuals per year, higher than that of other known bottlenose dolphin populations, with a calving interval between 2.45 and 3.5Â years. These results will be useful for projecting future trends of this (sub)population.